Regional Climate Studies of China - Fu, Congbin; Jiang, Zhihong; Guan, Zhaoyong; He, Jinhai; Xu, Zhongfeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Regional Climate of China is the first volume to present the latest research findings gained over the last decade which has greatly advanced our knowledge of the regional climate researches in China. A distinctive feature of the volume is that it is based on an integration of researches by using the advanced technologies, such as field observation and experiment, satellite information and numerical models in the regional climate studies.
Climate of China and East Asian Monsoon -- Paleoclimate of China -- Interdecadal Climate Variability in China Associated with the Pacific Decadal Oscillation -- Interannual Variability of Summer Climate of China in Association with ENSO and the Indian Ocean Dipole -- Aridity Trend in Northern China -- Effects of the Tibetan Plateau on the Climate of China -- Soil Moisture Variations and Its Impact on the Regional Climatic Change in China -- Climate Extremes and Related Disasters in China -- Regional Climate Modeling of China and East Asia -- Projection of Future Climate in China -- Impacts of Climate Change on Water Resources and Agriculture in China.
Keywords: Earth sciences; Meteorology; Atmospheric sciences; Geography; Air pollution; Earth Sciences; Atmospheric Sciences; Meteorology; Atmospheric Protection/Air Quality Control/Air Pollution; Geography, general; Electronic books